VD_FINDINFO Jug / 2012 / 125 vom 16. Mai 2012 - VD Tribunal cantonal (2012)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 15 al. 2 LPP, 73 al. 2 LPP, 7 OLP, 12 OPP2, 111 al. 1 LPA-VD